Correlates of procrastination and performance at work: The role of having "good fit". Issue 3 (3rd July 2018) - Metin, U. Baran; Peeters, Maria C. W.; Taris, Toon W.
Abstract: Occupational research often emphasizes the importance of workplace characteristics for understanding job stress and employee well-being, but the role of personal characteristics and having a good match with the job is mostly neglected. We explored how job crafting and feelings of being authentic at work were related to work engagement, work engagement of performance, and procrastination. A structural equation model analyzed self-reports from 380 Dutch office employees. Job crafting and authenticity were positively related to work engagement, and high work engagement predicted? better in-role and extra-role performance and less work procrastination. Moreover, performance and procrastination were negatively related. Results emphasize the importance of having a "good fit" between the employment settings and employees to promote engagement. By improving employee's work engagement, organizations might improve the likelihood that personnel respond favorably with organizational goals and reduce the chances of engaging in workplace procrastination.